Discrimination between Viable and Dead Encephalitozoon cuniculi (Microsporidian) Spores by Dual Staining with Sytox Green and Calcofluor White M2R - Green, L. C. (American Society for Microbiology, 2000)
Microsporidia are obligate intracellular parasites, recognized as causing chronic diarrhea and systemic disease in AIDS patients, organ transplant recipients, travelers, and malnourished children. Species of microsporidia that infect humans have been detected in drinking-water sources, and methods are needed to ascertain if these microsporidia are viable and capable of causing infections. In this study, Calcofluor White M2R and Sytox Green stains were used in combination to differentiate between live (freshly harvested) and dead (boiled) Encephalitozoon cuniculi spores. Calcofluor White M2R binds to chitin in the microsporidian spore wall. Dual-stained live spores appeared as turquoise-blue ovals, while dead spores appeared as white-yellow ovals at an excitation wavelength of 395 to 415 nm used for viewing the Calcofluor stain. Sytox Green, a nuclear stain, is excluded by live spores but penetrates compromised spore membranes. Dual-stained dead spores fluoresced bright yellow-green when viewed at an excitation wavelength of 470 to 490 nm, whereas live spores failed to stain with Sytox Green. After live and dead spores were mixed at various ratios, the number of viably stained spores detected in the dual-staining procedure correlated (P = 0.0025) with the expected numbers of viable spores. Spore mixtures were also assayed for infectivity in a focus-forming assay, and a correlation (P = 0.0002) was measured between the percentage of focus-forming microsporidia and the percentage of expected infectious spores in each mixture. By analysis of variance, no statistically significant differences were measured between the percentage of viably stained microsporidia and the percentage of infectious microsporidia (P = 0.964) in each mixture. These results suggest that Calcofluor White M2R and Sytox Green stains, when used together, may facilitate studies to identify viable microsporidia.